Update on immunotherapy for the treatment of asthma. Issue 1 (January 2016) - Canonica, Giorgio W.; Bagnasco, Diego; Ferrantino, Giovanna; Ferrando, Matteo; Passalacqua, Giovanni
Abstract : Purpose of review: Despite that specific immunotherapy can boast being more than a century old, there is still skepticism about its real effectiveness, and therefore it is still used too little in clinical practice. The purpose of this review was to analyze the most recent articles in the literature to highlight scientific evidence for the proper use of allergen immunotherapy (AIT). Recent findings: In the near future, the concept of medicine for trials will have to be revised and in certain cases abandoned in favor of a personalized medicine, able to use a drug more targeted for the individual patient and not for the disease. Summary: For AIT, it will become increasingly important to use products designed properly, standardized and with a well documented effectiveness in clinical studies. We must overcome the disputes of subcutaneous immunotherapy versus sublingual immunotherapy, arrive at the concept of personalized medicine regarding AIT, framing in different phenotypes of asthma patients to use the optimal preparation for each particular patient.